Tingkat Partisipasi dalam Kegiatan Pendidikan Kecakapan Hidup - Lina Asnamawati; Ninuk Purnaningsih; Soenarmo J. Hatmodjosoewito (Jurnal Penyuluhan, 2014)
Life skill education is an essential thing that must be owned by people to gain knowledge and practical skill in particular work fields. The success of life skill education was determined by the direct involvement of the society based on the planning, implementation, evaluation, and benefit of the result. The society would have involved in an activity if it was appropriate with the necessity, the interest, the aptitude, and the availability and the continuity of the source so that the society can apply the skill and the knowledge which are required for themselves and are useful for teaching the local society. The participation of the society was influenced by age, level of formal and informal education, attitude toward life skills, level of knowledge of life skills, functional skills, previous experience about life skills, the guidance of facilitators, and also the availability of supported facilities. According to Arstein, the participation of the society included in tokenism group which is the involvement due to the push in order to make them agree, the announcement of the same direction, the advice from the society is accepted but anyhow it became useless. The degree of the participation from the society gives much effect toward the success of life skill education in attitude change related to personal skill and academic skill. The attitude is also seen in social and vocational skills.Keywords: the level participation, life skill